Plasma-Optical Effect in GaAs PIN Photodiodes - M. A. Grado Caffaro; M. Grado Caffaro (Active and Passive Electronic Components)
This paper is devoted to the analysis of the Plasma-Optical Effect in GaAs PIN photodiodes operating at the infrared range. An approximated expression for the variation of the refractive index in the intrinsic zone of a AsGa PIN photodiode is obtained. This variation is induced by the charge of the device. The approach developed by us is in a good agreement with experimental works. Moreover, an application concerning high-frequency ICs is outlined.